2004
DOI: 10.1093/chemse/bjh070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concentration on Taste-Taste Interactions in Foods for Elderly and Young Subjects

Abstract: An increase in concentration of one of the tastants in a 'real food' might affect not only the perception of the taste quality of that manipulated tastant but also the other perceivable taste qualities. The influence of concentration increase of sodium or potassium chloride in tomato soup, sucrose or aspartame in iced tea, acetic or citric acid in mayonnaise, caffeine or quinine HCl in chocolate drink, monosodium glutamate (MSG) or inosine 5'-monophosphate (IMP) in broth on the other perceivable taste qualitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…However, it has been difficult to relate higher optimal flavor concentration to lower performances in sensory tests (Koskinen et al 2003b;Forde and Delahunty 2004;Kremer et al 2005;Koskinen and Tuorila 2005). Besides, not all studies find positive effects of flavor enhancement on intake and liking in elderly people (Mojet et al 2004;Koskinen et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been difficult to relate higher optimal flavor concentration to lower performances in sensory tests (Koskinen et al 2003b;Forde and Delahunty 2004;Kremer et al 2005;Koskinen and Tuorila 2005). Besides, not all studies find positive effects of flavor enhancement on intake and liking in elderly people (Mojet et al 2004;Koskinen et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…26,27) According to a study of taste mixture interactions in human sensation testing reported by Green et al, the sourness of citric acid was not suppressed by quinine sulfate (bitterness standard). 27) Overall, these sources suggest that sour substances may be good bitterness suppressors without losing their own sour tastes.…”
Section: Discussionmentioning
confidence: 99%
“…For obtaining enhanced salty taste, flavour enhancing natural ingredients could be employed in food formulation which helps to obtain savory profile and rebalance the flavor of products containing low sodium along with contribution of increased saltiness perception [22]. Since salt reduction is known to have greater impact on flavour perception, an investigation on the flavour and textural properties of white bread containing 10-50% less sodium in which salt was replaced with fermented soy sauce at 25, 50 and 100% was conducted.…”
Section: Sensory Response For Control Productsmentioning
confidence: 99%